MANAJEMEN PENGORGANISASIAN PROGRAM KURSUS BAHASA ARAB DI PARE KEDIRI - Rahmawati, Alvi Dyah (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2018)
This study discusses about: 1) organizing management in Arabic course Al-Azhar Pare, 2) problems in organizing management in Arabic course institute Al-Azhar Pare. This was a descriptive qualitative research. The data were collected by interviews and documentation. Then the data were analyzed in three steps, 1) data reduction, 2) data presentation, 3) drawing conclusions / verification. The results of this research showed that the organizing management Arabic language course Al-Azhar Pare was still weak because of some obstacles such as the absence of clear organizational structure. Managers only gave the verbal division of duties to each member and did not create a chart of organizational structure for members so as to make the position between subordinates and bosses are invisible. Participants who had been granted certain rights were not given a clear number of members to assist in carrying out their duties. Thus, the organizing system is less organized.